Prevalence and risk factors of obstetric violence among Jordanian women: a cross-sectional study - Nour Alrida; Amal Ababneh; Muna Salahat; Yasmeen Abu-Sumaqa; Ahmad Rayan; Basheer Al-Zu'bi; Manar Abu-Abbas (Medicinski glasnik, 2025)
Aim: To assess the prevalence and risk factors associated with obstetric violence during childbirth among Jordanian women. Methods: A descriptive cross-sectional design was adopted. Recruitment occurred in public maternity and children’s health centres in the Irbid Directorate in Jordan. Five hundred and fifteen women were enrolled in the study as a convenient sample. An online questionnaire comprised socio-demographic, obstetric and clinical variables and obstetric violence measurement. Results: The prevalence of physical, verbal, and psycho-affective violence was reported in 390 (75.7%), 154 (29.9%), and 191 (37.1%) cases, respectively. Mode of delivery, using induction, and complicated delivery were significantly associated with physical violence (p<0.05). Place of last delivery (OR= 0.51 95% CI: 0.3-0.86), complicated delivery, and primary healthcare provider were associated with exposure to verbal violence (p<0.05). Psycho-affective violence was significantly associated with the mode of delivery, complicated delivery, and primary healthcare providers (p< 0.05). Conclusion: The findings of this study, which showed a high prevalence of physical, verbal, and psycho-affective violence, underscore the urgent need to create possible solutions that guarantee the global goal of respectful maternal treatment. These findings are significant as they highlight the prevalence of obstetric violence among Jordanian women and the associated risk factors, thereby contributing to the growing body of research on this critical issue.
Keywords: Childbirth; Maternal Health Services; obstetric; patient safety; violence